Comparison of the Effectiveness of Imago Therapy and Cognitive-Behavioral Couple Therapy on Dimensions of Care in Relationships and Psychological Capital in Working Couples - Ghamari , Mostafa; Mollazadeh, Alireza; Davoudi, Hossein (Iranian Journal of Neurodevelopmental Disorders, 2024)
Purpose: The purpose of this study was to compare the effectiveness of Imago therapy and cognitive-behavioral couple therapy on the dimensions of care in relationships and psychological capital in working couples.Methods and Materials: This study employed an experimental design with a pre-test, post-test, control group, and follow-up. The statistical population comprised all working teacher couples in Tuyserkan, located in Hamadan Province, who were employed during the 2021–2022 period. From this population, 40 individuals were randomly selected and distributed into four groups (two experimental groups and two control groups), with 20 participants in the experimental groups and 20 in the control groups. The experimental groups received training through 10 sessions of Imago therapy and 10 sessions of cognitive-behavioral couple therapy, with each session lasting 90 minutes. The control groups did not receive any training. Data were collected using the Dimensions of Care in Relationships Questionnaire and the Psychological Capital Questionnaire. Multivariate repeated measures analysis of variance was used to analyze the study findings.Findings: The results of the data analysis indicated that both Imago therapy and cognitive-behavioral couple therapy had a significant effect on the dimensions of care in relationships and the psychological capital of working couples (p < 0.05).Conclusion: The findings of this study demonstrated that there was no significant difference between the effectiveness of Imago therapy and cognitive-behavioral couple therapy on the dimensions of care in relationships and psychological capital.